Facile one-pot synthesis of novel spherical zeolite-reduced graphene oxide composites for cationic dye adsorption - Zhu, J.; Wang, Y.; Liu, Jian; Zhang, Y. (American Chemical Society, 2014)
Zeolite-reduced graphene oxide (zeolite-rGO) composites were first fabricated from halloysite nanotubes (HNTs) by blending with GO via a hydrothermal reaction and then were used as an effective adsorbent for the removal of cationic dyes (methylene blue and malachite green). Zeolite-rGO was presented as having spherical structure with the diameter of 2-2.5 µm. The adsorption behavior of the two cationic dyes was affected by equilibrium time, pH, etc. Additionally, the most appropriate adsorption process of dyes was well-fitted to Langmuir models. It was found that adsorption of dyes was favorable and the maximum adsorption capacity of methylene blue reached 53.3 mg g-1 (48.6 mg g-1 for malachite green). The superior behavior of zeolite-rGO for cationic dye removal from an aqueous solution should be amenable to potential water treatment applications in consideration of zeolite-rGO's low-cost, abundance in clay minerals, and favorable adsorption processes. © 2014 American Chemical Society.